“EduKation demenz® Nursing” in the acute hospital setting. Evaluation of a dementia training program: a pilot study - Gehr, Thomas; Sieber, Cornel; Freiberger, Ellen; Engel, Sabine Alexandra (Zeitschrift für Gerontologie und Geriatrie, 2021)
Background: An increasing number of people with dementia (PwD) are being hospitalized due to acute conditions. The surrounding conditions and procedures in acute hospitals are not oriented to the special needs of this vulnerable patient group. The behavior of PwD poses particular challenges and burdens for nursing staff. Objective: The aim of this pilot study was to evaluate the effectiveness of a 2-day dementia training program with a self-reflection component compared to a standard 1.5‑h training of nursing staff caring for PwD in acute hospitals. Methods: A nonrandomized pretest-posttest study with a control group was conducted in three German acute hospitals. Through a questionnaire, nursing staff caring for PwD were examined for potential changes in attitude, strain and confidence levels. The intervention group (n = 32) received a 2-day training program, “EduKation demenz® Nursing”, the control group (n = 36) participated in a short,1.5‑h dementia training. Results: Compared to the control group, the intervention group demonstrated statistically significant improvement in perceived strain (p = 0.007) and in confidence in caring for PwD (p < 0.001). There were positive but not significant changes in attitude (p = 0.176). Conclusion: “EduKation demenz® Nursing”, a 2-day training program with a self-reflection component, could provide more effective support for nursing staff in acute hospitals caring for PwD than a 1.5‑h training. Results indicate, however, that general conditions in acute hospitals should be changed to allow nursing staff to apply the knowledge gained.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Dementia-sensitive care; Intervention; Qualification; Self-reflection; Strain